Majasi berkelok: mengembangkan kearifan lokal dalam pengelolaan pembelajaran inklusif di sekolah menengah - Famella, Shelvie; Monia, Fenny Ayu; Anita, Anita (Indonesian Institute for Counseling, Education and Theraphy, 2024)
This study aims to measure the effectiveness of the local wisdom-based inclusive school learning management model on students in inclusive classrooms. The focus of the research also includes assessing whether the character values contained in Gurindam Dua Belas can be applied in everyday life by students. The method used is observation with indicators that include character values such as Islam, behavior/faith, social, character, usefulness, ethics, leadership, and leadership. The results of the observation recapitulation show positive changes in student behavior in inclusive classes and an increase in character values. Furthermore, the local wisdom-based inclusive school learning management model book has been declared valid and practical by education experts. The practicality of this model has also been tested and approved by users. The results indicate that this management model has the potential to improve learning effectiveness in inclusive schools and promote better character values in students.